2012
DOI: 10.1038/nature11647
|View full text |Cite
|
Sign up to set email alerts
|

Towards germline gene therapy of inherited mitochondrial diseases

Abstract: Mutations in mitochondrial DNA (mtDNA) are associated with serious human diseases and inherited from mother's eggs. Here we investigated the feasibility of mtDNA replacement in human oocytes by spindle transfer (ST). Of 106 human oocytes donated for research, 65 were subjected to reciprocal ST and 33 served as controls. Fertilization rate in ST oocytes (73%) was similar to controls (75%). However, a significant portion of ST zygotes (52%) displayed abnormal fertilization as determined by irregular number of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
352
3
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 382 publications
(373 citation statements)
references
References 23 publications
(35 reference statements)
6
352
3
9
Order By: Relevance
“…Controlled ovarian stimulation. Research oocyte donors were evaluated before study inclusion as previously reported; standard IVF protocols and procedures for ovarian stimulation were described previously 44 . Oocyte donation cycles were managed by OHSU Fertility physicians.…”
Section: Methodsmentioning
confidence: 99%
“…Controlled ovarian stimulation. Research oocyte donors were evaluated before study inclusion as previously reported; standard IVF protocols and procedures for ovarian stimulation were described previously 44 . Oocyte donation cycles were managed by OHSU Fertility physicians.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we utilized fresh MII oocytes donated by and retrieved from 11 healthy volunteers (25-31 years) following controlled ovarian stimulation (COS) protocols and transvaginal follicular aspirations (Tachibana et al, 2013b).…”
Section: De Novo Formation Of MII Spindles From the Pb1 Genomesmentioning
confidence: 99%
“…21). Yet, there are regulatory means in place that in fact prevent human germline modifications in publicly funded research and in clinical settings.…”
Section: Illusion Of (Universal) Controlmentioning
confidence: 99%